1994
DOI: 10.1002/eji.1830240820
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐specific T cells are a predominant component of islet infiltrates in pre‐diabetic NOD mice

Abstract: Numerous investigation have demonstrated that T cells are involved in destruction of beta cells in the NOD mouse, a widely studied model of type I diabetes. In this report we describe a series of islet-specific T cell lines established from islet-infiltrating lymphocytes obtained from individual pre-diabetic NOD mice as well as a large panel of clones derived from these lines. Proliferation assays indicated that these nominally islet-specific lines responded vigorously to porcine insulin. Furthermore, of 40 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(198 citation statements)
references
References 28 publications
5
190
1
Order By: Relevance
“…The observations that overt diabetes is often preceded by autoantibodies reactive to insulin (20) and that islet-infiltrating cells isolated from NOD mice are enriched in insulin-specific T cells (21) suggest that an immune -1,2ϩ (A, B) and Thy-1,1ϩ (C, D). Original magnifications ϫ250.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations that overt diabetes is often preceded by autoantibodies reactive to insulin (20) and that islet-infiltrating cells isolated from NOD mice are enriched in insulin-specific T cells (21) suggest that an immune -1,2ϩ (A, B) and Thy-1,1ϩ (C, D). Original magnifications ϫ250.…”
Section: Discussionmentioning
confidence: 99%
“…The nonobese diabetic (NOD) mouse spontaneously develops an autoimmune disease sharing immunological and histopathological similarities with type I insulin-dependent diabetes mellitus in humans (19)(20)(21)(22). Prolonged feeding of large (milligram) amounts of heterologous insulin has been shown to delay the onset of diabetes in NOD mice (23).…”
mentioning
confidence: 99%
“…Insulin, and particularly the 9-23 peptide of the insulin beta chain, is a primary target of T cell reactivity in both the human disease and the NOD mouse [38,39] (in this issue, contribution by Eisenbarth). Initial binding studies of the B:(9-23) peptide to soluble I-A g7 in detergent free conditions revealed poor binding and fast dissociation rates [10,13,14,40].…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thmentioning
confidence: 99%
“…Pathogenic T cells specific for these 2 antigens are present in significant numbers in infiltrated islets of NOD mice (which develop spontaneous IDDM) and exhibit efficient diabetogenic properties, as demonstrated by their capacity to transfer disease to immunoincompetent syngeneic recipients (9)(10)(11)(12)(13). Two different transgenic animal models were analyzed: NOD-PI mice, which overexpress proinsulin 2 in their APCs (14), and NOD-IGRP mice, which overexpress IGRP in their APCs.…”
Section: Epitope Spreading In Autoimmune Diabetes: From Proinsulin Tomentioning
confidence: 99%